Detection and Classification Techniques of Citrus Leaves Diseases: A Survey - Roheet Bhatnagar, Devesh Kumar Srivastava, Ashok Kumar Saini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Agricultural production is essential to the economic development of any country. That’s why disease identification in plants is critical in the agricultural sector, as a disease in plants is a regular occurrence. If reasonable precautions are not taken on time, plants can significantly affect the environment, affecting product quality, quantity, and productivity. Lemons, grapes, limes, oranges, etc., are common citrus fruits grown the entire world. About 50% of citrus fruits are wasted each year because of diverse plant sicknesses. This paper offers a survey of various approaches for detecting and classifying diseases in citrus plant leaves. A comprehensive taxonomy of citrus leaf diseases is also presented. A study of automatic illness recognition and classification methods are also discussed. We explore different methods for pre-processing, segmentation, extraction of features and grouping. Discuss also the relevance of functional extraction and techniques of deep learning.